1993
DOI: 10.1007/bf01232747
|View full text |Cite
|
Sign up to set email alerts
|

Multiple regulatory elements ensure accurate transcription of a human ribosomal protein gene

Abstract: Previously we have shown that expression of a cloned human ribosomal protein gene, RPS14, depends upon regulatory sites located within the gene's proximal upstream DNA plus its first intron. In order to identify cis-active sequence motifs within the RPS14 promoter-enhancer complex, we transiently expressed a set of informative deletion clones in cultured Chinese hamster ovary cells. These experiments revealed three DNA sequence motifs that surround the S14 mRNA initiation site and are necessary for accurate tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…However, transcriptional control of rp genes has been observed during mouse myoblast dierentiation, suggesting the presence of regulatory elements in the promoter regions of the rp genes in muscle cells that may be aected by dierentiation status (Agrawal and Bowman, 1987). Moreover, NFa1 (E2F) and NF-b1 recognition sequences have been found in diverse mammalian housekeeping genes including ribosomal proteins (Overman et al, 1993). These results support the hypothesis that multiple mechanisms may underlie the regulation of ribosomal proteins during cell growth arrest and dierentiation in dierent cell types.…”
Section: Discussionsupporting
confidence: 74%
“…However, transcriptional control of rp genes has been observed during mouse myoblast dierentiation, suggesting the presence of regulatory elements in the promoter regions of the rp genes in muscle cells that may be aected by dierentiation status (Agrawal and Bowman, 1987). Moreover, NFa1 (E2F) and NF-b1 recognition sequences have been found in diverse mammalian housekeeping genes including ribosomal proteins (Overman et al, 1993). These results support the hypothesis that multiple mechanisms may underlie the regulation of ribosomal proteins during cell growth arrest and dierentiation in dierent cell types.…”
Section: Discussionsupporting
confidence: 74%
“…Although large deletion mutations surrounding the NF-~31-binding site (such as between the BamHI and SmaI sites illustrated in Fig. 1) abrogated S14 transcription completely, site-specific deletions within the ~31 protein-binding site reduced transcription only partially {Overman et al 1993). For this reason, we proposed that the RPS14 downstream regulatory array is likely to be composed of multiple, cis-active functional elements, only one of which (the 131-binding site) is detected by electrophoretic methods used conventionally to assess DNA-protein interactions.…”
mentioning
confidence: 99%
“…Previously, we had reported that full-length S14 mRNA is the only transcript initiated from the sense strand of this human chromosome segment (Rhoads and Roufa 1987;Overman et al 1993). Therefore, our current experiments focused on a search for antisense RNAs that might derive from the RPS14 regulatory intron.…”
mentioning
confidence: 99%
See 2 more Smart Citations